2016
DOI: 10.1002/oby.21417
|View full text |Cite
|
Sign up to set email alerts
|

Ideals versus reality: Are weight ideals associated with weight change in the population?

Abstract: Objective: To quantify weight ideals of young adults and to examine whether the discrepancy between actual and ideal weight is associated with 10-year body mass index (BMI) change in the population. Methods: This study comprised 4,964 adults from the prospective population-based FinnTwin16 study. They reported their actual and ideal body weight at age 24 (range 22-27) and 10 years later (attrition 24.6%). The correlates of discrepancy between actual and ideal body weight and the impact on subsequent BMI change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
(63 reference statements)
1
9
0
Order By: Relevance
“…The characteristics of our participants in their mid-twenties are presented in Table 1. As previously reported, women on average weighted 61 kg and men 77 kg, and their mean BMIs were 22.2 and 23.9, respectively (Table 1) (Kärkkäinen et al 2016). Waist circumference was on average 75 cm among women and 85 cm among men.…”
Section: Resultssupporting
confidence: 76%
“…The characteristics of our participants in their mid-twenties are presented in Table 1. As previously reported, women on average weighted 61 kg and men 77 kg, and their mean BMIs were 22.2 and 23.9, respectively (Table 1) (Kärkkäinen et al 2016). Waist circumference was on average 75 cm among women and 85 cm among men.…”
Section: Resultssupporting
confidence: 76%
“…To date, it remains controversial whether factors that explain successful weight loss or maintenance differ in women and men (Stroebele-Benschop et al, 2013). Yet, our previous study showed that women and men perceive their weight differently (Kärkkäinen, Mustelin, Raevuori, Kaprio, & Keski-Rahkonen, 2016), and other researchers have suggested that women and men respond differently to weight maintenance and weight loss approaches (Robertson et al, 2016).…”
Section: Introductionmentioning
confidence: 73%
“…The actual (self-reported)–ideal body weight discrepancy was assessed by subtracting the actual body weight (self-reported) from the ideal body weight. Similar procedure of assessing body weight discrepancies was applied in the previous studies [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous research [9,14,15] on body weight perceptions have most often used self-reported discrepancies since they are easier to asses than objectively measured discrepancies. Indeed, some studies indicated that the objective reality (actual body weight) is a weaker correlate of future BMI than the subjective perception of that reality (perceived body weight) [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation